Adaptation, Commissioning, and Evaluation of a 3D Treatment Planning System for High-Resolution Small-Animal Irradiation. (June 2016) - Jeong, Jeho; Chen, Qing; Febo, Robert; Yang, Jie; Pham, Hai; Xiong, Jian-Ping; Zanzonico, Pat B.; Deasy, Joseph O.; Humm, John L.; Mageras, Gig S.
Although spatially precise systems are now available for small-animal irradiations, there are currently limited software tools available for treatment planning for such irradiations. We report on the adaptation, commissioning, and evaluation of a 3-dimensional treatment planning system for use with a small-animal irradiation system. The 225-kV X-ray beam of the X-RAD 225Cx microirradiator (Precision X-Ray) was commissioned using both ion-chamber and radiochromic film for 10 different collimators ranging in field size from 1 mm in diameter to 40 × 40 mm 2 . A clinical 3-dimensional treatment planning system (Metropolis) developed at our institution was adapted to small-animal irradiation by making it compatible with the dimensions of mice and rats, modeling the microirradiator beam orientations and collimators, and incorporating the measured beam data for dose calculation. Dose calculations in Metropolis were verified by comparison with measurements in phantoms. Treatment plans for irradiation of a tumor-bearing mouse were generated with both the Metropolis and the vendor-supplied software. The calculated beam-on times and the plan evaluation tools were compared. The dose rate at the central axis ranges from 74 to 365 cGy/min depending on the collimator size. Doses calculated with Metropolis agreed with phantom measurements within 3% for all collimators. The beam-on times calculated by Metropolis and the vendor-supplied software agreed within 1% at the isocenter. The modified 3-dimensional treatment planning system provides better visualization of the relationship between the X-ray beams and the small-animal anatomy as well as more complete dosimetric information on target tissues and organs at risk. It thereby enhances the potential of image-guided microirradiator systems for evaluation of dose–response relationships and for preclinical experimentation generally.